Learning Qowaid Arabiyah in the Alac Program (Afternoon Lesson Advisory Council) - Syariful Hikam, Faris; Hobsoh; Susilo, Agus; Ni'mah, Khoirin (Shaut al Arabiyyah, 2025)
This study aims to describe the reasoning ability in the field of learning Qowaid Arabic in the ALAC (Afternoon Lesson Advisory Council) program. The learning taken here is using Qowaid Arabic, Qowaid here is nahwu which is paired with shorof, so that it becomes nahwu shorof, which is a science that reviews the grammar (basics) of Arabic grammar. In other words, the discussion of Qowaid Arabic cannot be separated from these two terms. Therefore, learning using Qowaid Arabic is the right way. The research method used is a qualitative method and data collection is carried out through observation, interviews and documentation. The subjects of the study were all students at Madrasah Ummul Quro At-tarbawiyah putri, totaling 51 people. In this study, Qowaid Arabic Learning is not like other lessons, namely the teacher tells students to write in good and correct Arabic writing. This learning process is an assistance provided by educators so that the process of acquiring knowledge, mastery of skills and habits, and the formation of attitudes and beliefs in students can occur. the results of this study can be concluded that in the Implementation of Qowaid Arabiyah learning in improving the quality of students in understanding Arabic at Madrasah Ummul Quro At-Tarbawiyah putri Plakpak Pagantenan Pamekasan. namely starting with First, the opening filled with Nadzoman. Second, class attendance. Third, introduction of the material by reading the material to the students first, after that the teacher reads one by one either in the form of small or easy mufradat as Qowaid material such as examples after that students are asked to write in their respective books and provide positions in the examples. Therefore, it is necessary to have a program in learning Qowaid Arabiyah, namely the ALAC (Afternoon Lesson Advisory Council) program. ALAC (Afternoon Lesson Advisory Council) is a learning program that is implemented in the afternoon where the ALAC program is focused on studying Qowaid-Qowaid Arabiyah.